Undergraduate Students’ Self-Esteem and Motivation in Relation to Their English-Speaking Proficiency - Islamiah, Neneng; Hasbi, Muhamad (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This study aimed to investigate whether the combination of students’ self-esteem and students’ motivation significantly explains their English-speaking proficiency, both separately and simultaneously. For this purpose, 38 students were selected among the undergraduate students of the Islamic Study Faculty, University of Muhammadiyah Prof. Dr. Hamka, Indonesia. A quantitative analysis was applied. To measure the students’ self-esteem and motivation, modified questionnaires were used, while their English-speaking proficiency was evaluated by two raters. The result showed a significant influence of the combination of the two variables on the dependent variable; English speaking proficiency. It indicated from the calculation by using SPSS version 17.00 which showed that the value of F-observed 11.463 is more than F-critical (3.27). The multiple correlation jointly between X1 and X2 and Y (Ry12) by 0.629 is significant. Moreover, the R-squared value of 0.396 can be interpreted that self-esteem and motivation together account for 39.6% of the variation in students’ English-speaking proficiency.